Legal Aid for the Victims of Domestic Violence: Problems and Challenges - Wicaksono, Sonny Saptoajie; Soebiakto, Gabrielle Poetri; Arifin, Ridwan (The Indonesian Journal of International Clinical Legal Education, 2021)
The number of domestic violence from year to year continues to increase. Many studies show that the increasing trend is motivated by many factors, one of which is the economy. This study aims to analyze the provision of legal aid for victims of domestic violence. This research is one of the community services programs in collaboration with the Center for Legal Aid, Faculty of Law, Universitas Negeri Semarang. This study shows that access to legal aid for victims of domestic violence has not been evenly distributed. This is due to several factors, ranging from not being exposed to cases of domestic violence, to the lack of information on legal aid for victims.